Enriching Students' Speech When Studying Russian Literature in Schools (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines specific problems related to the study of Russian literature in Uzbek schools. The author focuses on the main factors of interaction and mutual influence of language and literature, which operate in close interaction and are considered in individual modules only in order to more reliably reveal the individual aspects of the single process of mastering the treasures of Russian literature by schoolchildren. The enrichment of speech with phraseological units should correspond to the psychological and pedagogical characteristics of a certain age of students and meet certain criteria outlined in the article.